A Reanalysis of Occupation and Suicide: Negative Perceptions of the Workplace Linked to Suicide Attempts. Issue 8 (17th November 2017) - Howard, Matt; Krannitz, Morgan
ABSTRACT: Suicide is the ultimate outcome of poor psychological well-being; however, there is a paucity of research examining the link between occupation and suicide, despite early academic interest and the known importance of work to our everyday lives. We propose that this body of research was abandoned prematurely, and we provide a reanalysis by integrating the Job Characteristics Model and the Conservation of Resources model with extant suicide research. Specifically, we hypothesize that work design characteristics (job autonomy, task variety, physical demands) and threats to personal resources (absence of viewing work-as-career, work-family conflict, family-work conflict, job dissatisfaction) are linked to suicide attempts via depression and suicidal ideation. Utilizing three measurement occasions and 2, 855 participants from the AddHealth database, our findings indicate that job autonomy, task variety, work-family conflict, family-work conflict, and job dissatisfaction all indirectly contribute to employees' suicide attempts via depression and suicidal ideation. Thus, negative employee perceptions of the workplace environment have much more severe consequences than is typically examined. Based on these results, we provide recommendations for developing a theoretically derived nomological net around suicidal behavior in an organizational context, and offer strategies for managers and employees to construct a work environment that is conducive to employee well-being.